Cultural-Religious Integration in Civic Education Assessment: Validation of Rights and Obligations Evaluation Instruments in Islamic Elementary Schools - Anggraini, Alfina; Astari, Nasa Bela; Zakiyyah, Zahra; Rahmayanti, Novita Sri; Nabilah, Salwa; Fajriah, Sabrina Nurul; Sukmawati, Wati (Actual Insight, 2026)
This research examines the validity of culturally-responsive evaluation instruments employed in Civic Education (PPKn) learning, specifically focusing on rights and obligations among third-grade students at MI Annur, West Jakarta. This research addresses the critical gap in empirical validation of PPKn assessment tools that integrate both civic competencies and Islamic moral-spiritual frameworks. Two culturally-aligned instrument types were utilized: cognitive test instruments measuring students' conceptual understanding of rights and obligations within Islamic ethical frameworks, and non-test questionnaires assessing attitudinal development and character application in daily school contexts. Results demonstrate that 87% of test items and 91% of questionnaire items exhibited high validity coefficients (r > 0.30), indicating strong cultural-pedagogical alignment. However, the study revealed a significant disconnect between cognitive understanding and attitudinal implementation among some students, highlighting the complexity of value internalization in dual religious-secular educational systems. These findings provide practical implications for curriculum developers working in Islamic educational contexts and offer validated frameworks for developing culturally-embedded assessment tools that bridge civic education with religious moral development, contributing to broader conversations about citizenship education in culturally diverse societies.